Multi-branched benzylidene ketone based photoinitiators for multiphoton fabrication - Zhang, Fan; Hu, Q.; Castanon, A.; He, Y.; Liu, Y.; Paul, B.T.; Tuck, C.J.; Hague, Richard J.M.; Wildman, Ricky D. (Elsevier, 2017)
In this article, we report the synthesis of a series of multi-branched benzylidene (BI) ketone-based photo-initiators for two-photon polymerisation based 3D printing/additive manufacturing. Resins prepared by the addition of 1 wt.% of these initiators were processed in a commercial 2 photon polymerisation system to fabricate 3D woodpile structures, the qualities of which were examined to determine the efficiencies of the initiators. The results showed that compared to commercial initiator Irgacure 369, the four-branched initiator 4-BI exhibited excellent performance with higher writing speeds and broader ideal processing windows. The successful fabrication of complex 3D structures at high writing speeds (up to 100 mm/s) indicated that the four-branched initiator 4-BI could potentially increase the fabrication efficiency and hence become a promising initiator for two-photon polymerisation.